CARBONATE ISOTOPE CHEMOSTRATIGRAPHY SUGGESTS REVISIONS TO THE GEOLOGICAL HISTORY OF THE WEST FINNMARK CALEDONIDES, NORTHERN NORWAY - Slagstad T.; Melezhik V.A.; Zwaan K.B.; Roberts D.; Kirkland C.L.; Gorokhov I.M.; Fallick A.E. (My University, 2006)
Strontium and and carbon isotopic data from amphibolite-facies marbles of the Falkenes formation, Sørøy succession (structurally upper Kalak Nappe Complex) in West Finnmark, northern Norway, indicate that the marbles were deposited between 760 and 710 Ma. Marbles of similar age have previously been identified only in the Uppermost Allochthon in north-central Norway, where they are considered to have a Laurentian ancestry. A similar origin and tectonostratigraphic position appears likely for the Falkenes formation. In contrast, structurally lower units within the Kalak Nappe Complex appaer to have Baltican affinities. This dichotomy requires that commonly held ideas regarding the tectonostratigraphy of the West Finnmark Caledonides be revised. Combines with recent U-Pb dating of zircon and monazite from rocks associated with the marbles, the isotopic data suggest that the Sørøy successsion of the Kalak Nappe Complex is not a continuous, depositional sequence as previously thought, but rather consists of a number of disparate and probably unrelated thrust-sheets, assembled during Late Silurian, Scandinavian orogenesis. This work shows that the West Finnmark Caledonides, and contributes to already existing data that may allow 'chemostratigraphic' correlation and reconstruction of the Caledonian belt.
Keywords: Silurian; Paleozoic::Silurian; Палеозой::Силурийская